EFFECT OF pH AND HEAT TREATMENT ON PHYSICOCHEMICAL CHARACTERISTICS OF SODIUM PHOSPHOCASEINATE POWDER - R. Perveen; M. S. Butt; N. Huma; H. Nawaz (Journal of Animal and Plant Sciences, 2015)
The present study was conducted to check the effect of alkalinization (pH 8 to 11), acidification (pH 6- 4) and temperature (60, 65, 70, 75, 80, 85 and 90ºC) on size, charge and viscosity of sodium phosphocaseinate powder after rehydrated in deionized water @ 3, 4 and 5% concentration at room temperature. The particle size distribution was determined by master sizer, while, size and charge of different phosphocaseinate solutions were assessed through zeta sizer. Moreover, the viscosity was monitored by viscometer. Alkalinization significantly affected the size of casein micelles; with minimum size noted at pH 11 in the tested solutions. Moreover, charge of casein micelles decreased with the progressive rise in pH of various solutions. The mean values at pH 11 for 3, 4 and 5% solutions were -28.35, -20.55, -29.09 mV, correspondingly. Acidification resulted in increased size of casein micelles. Heat treatment resulted in decreased size and charge of casein micelles. The mean values for casein micelles size at 90оC for 3, 4 and 5% solutions were 255.50, 260.55 and 289.71 nm, respectively. Likewise, charge was observed as -15.25, -15.85 and -14.85 mV in respective manner. The decreasing trend of pH from 6.9 to 5.5 elucidated maximum viscosity 1.59-1.80 cP in 5% solution as compared to 3% (1.28 to 1.60 cP) and 4% (1.47 to 1.74 cP). Conclusively, the physicochemical conditions such as low pH or high temperature cause conformational changes in protein, leading to aggregation and precipitation. These information will help processers to formulate innovative protein enriched dairy and non-dairy products.
Keywords: Acidification; Alkalinization; Viscosity; Size; Charge